Neoanalysis, Orality, and Intertextuality: An Examination of Homeric Motif Transference - Jonathan, Burgess (Center for Studies in Oral Tradition, 2018)
In Homeric studies scholars have speculated on the influence of (non-surviving) preHomeric material on the Iliad. This article expands this line of argument from an oralist perspective, with reference to modern intertextual theory. It concludes that preHomeric and nonHomeric motifs from oral traditions were transferred into the epic poem, creating an intertextually allusive poetics that would have been recognizable to an early Greek audience informed of mythological traditions.